Current prospects of urine cytology in diagnosis and follow-up urinary tract malignancies - the short review - Jarosz, Piotr Michał; Oszczędłowski, Paweł; Pytka, Michalina; Nowaczek, Justyna; Jodłowska-Jędrych, Barbara (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Cytology of urine sediment is a diagnostic tool used to screen for urinary tract lesions in two cases: surveillance of patients with a history of urothelial malignancies and patients with unexplained, new onset haematuria. Since 2015 histopathological laboratories have been able to report urine cytology according to The Paris System (TPS). Current studies suggest usefulness of urinary cytology in follow-up of urinary tract malignancies, especially urinary bladder cancer, which is the 13th most deadly throughout the world being responsible for 200 000 deaths in 2018 among neoplasms. Objective: To review currently available data on PubMed about usefulness urine cytology reporting in follow-up and diagnosis of urinary tract malignancies. A brief description of the state of knowledge: Advantages of urine cytology examination contain non-invasiveness, high specificity, lower cost than cystoscopy and enable immunohistochemistry performance as well. Implementation of The Paris System for reporting urine cytology has created an universally acceptable and globally used report system. Reporting according to TPS significantly reduced the number of cases described as atypical changes. Conclusions: Urinary cytology is used to supplement endoscopic evaluation of the urinary tract in the screening and the surveillance of urothelial carcinoma. The Paris System for reporting urinary cytology has clarified the diagnostic categories of urine sediment examination. Cystoscopy and urine cytology are the standard tools for monitoring urinary tract malignancies.